A simple "neural induction" model with two interacting cleavage-arrested ascidian blastomeres. - Okado, H (1988)
A single anterior-animal blastomere, which includes the presumptive neural region in the eight-cell embryo of the Halocynthia, a protochordate, when dissociated, cleavage-arrested with cytochalasin B, and cultured in isolation, differentiated exclusively to epidermal type judging from membrane excitability and immunoreactivity. However, when the same blastomere was cultured in contact with a single anterior-vegetal blastomere, which includes the presumptive notochordal region, it displayed Na spikes and showed no expression of the epidermal antigen, suggesting that "neural induction" resulted in a single cell during the interaction with a single neighboring cell. This simple two-cell system can be used for further studies on the induction mechanism.